2019
DOI: 10.1016/j.firesaf.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A review of tunnel fire research from Edinburgh

Abstract: The University of Edinburgh and its alumni have made significant contributions to knowledge in the field of tunnel fire safety engineering. This paper summarises the situation of tunnel fire safety in the early 1970s, when the department of fire engineering was founded and briefly discusses all the contributions to knowledge in the field, made by Edinburgh and its alumni in the past four decades. Research carried out at Edinburgh has changed the way the tunnel safety industry estimates heat release rates in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…By the 1950s, studies on tunnel fire were still limited and mainly focused on construction safety (ANDERSON, 1936), ventilation systems (Ole and Cruthers, 1947), and fire protection systems (Sevcik, 1928). Since then, more and more fire research have been conducted in tunnels of different scales, and new tunnel fire safety codes have been applied to alleviate and limit the threats of toxic gases and smoke (Carvel, 2019). For all these studies, the most important issue is the efficiency of the Fixed Fire Fighting System (FFFS), particularly the ventilation system, that ensures the safety of evacuees.…”
Section: Tunnel Fire Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…By the 1950s, studies on tunnel fire were still limited and mainly focused on construction safety (ANDERSON, 1936), ventilation systems (Ole and Cruthers, 1947), and fire protection systems (Sevcik, 1928). Since then, more and more fire research have been conducted in tunnels of different scales, and new tunnel fire safety codes have been applied to alleviate and limit the threats of toxic gases and smoke (Carvel, 2019). For all these studies, the most important issue is the efficiency of the Fixed Fire Fighting System (FFFS), particularly the ventilation system, that ensures the safety of evacuees.…”
Section: Tunnel Fire Researchmentioning
confidence: 99%
“…Tunnels have played an essential role in modern transportation systems since the mid-20th century, owing to their high utility and flexibility in mountainous areas and their effectiveness in tackling the tight land supply of crowded metropolitan areas. However, as a significant infrastructure hazard, fires in tunnels cause a great deal of economic and social losses each year (Beard and Carvel, 2012;Carvel, 2019;Casey, 2020;Ingason et al, 2015a;Li and Liu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fire is an important subject for a wide range of design, operation and maintenance processes of tunnels. Many historical fire incidents have confirmed that, while tunnel fires may not necessarily cause the collapse of a tunnel structure, significant damage can occur to the tunnel lining, and such damage in turn can result in long-term disruption to traffic or rail services leading to major economic losses (Carvel, 2019;Casse and Caroly, 2019;Hua et al, 2021;Ren et al, 2019;Zhang et al, 2021a;b). For instance, in 2001 two trucks crashed and this triggered a fire and induced serious structural damage at the Gotthard Road Tunnel in Switzerland (Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The proper management of risk in underground mining, especially coal, is critical to avoid undesirable situations that could lead to tragic accidents, such as fires or explosions [1,2]. Many preventive and corrective measures have been proposed and developed over time [3], but there are still important fatalities in these types of activities [4].…”
Section: Introductionmentioning
confidence: 99%